Would fewer people drive to work in a city without excess commuting? Explorations in the Paris metropolitan area. (January 2017) - Korsu, Emre; Le Néchet, Florent
Highlights: An original way to explore the issue of excess commuting. A simulation-based approach to estimating the share of car use in trips-to-work under the hypothesis of commute minimisation. Pioneering research on excess commuting in the case of the Paris Metropolitan Area. In the Paris Metropolis, cutting average commuting distance could result in an increase in commuting by car. Minimising commute length converts many long-range trips by public transport into mid-range trips by car. Abstract: Urban planners have explored many solutions for reducing the energy and environmental costs of daily mobility in cities and one of them is to encourage households to embrace more efficient commuting patterns. As research on "excess commuting" has shown, the spatial distribution of housing and jobs in many cities would theoretically allow much shorter commuting distances than are actually observed. The question this paper tackles is how a more efficient commuting pattern would affect the transport modes workers use to travel to work. If workers and jobs were rematched in such a way as to minimise average commute distance, how would such a change impact the way people travel to work? While one might easily imagine an increase in the share of trips covered by soft modes of transport, there are reasons to believe that in some cases there might also be unexpected outcomes such an increase in car use. So how would people travel to work in a city where there is no "excess commuting"? We looked for an answer to this question through empirical simulations in the case of the Paris Metropolitan Area.